2020
DOI: 10.7150/thno.40715
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralized Bimetallic Oxide Nanotheranostics for Multimodal Imaging-Guided Combination Therapy

Abstract: The hypoxia of the tumor microenvironment (TME) often hinders the effectiveness of cancer treatments, especially O2-dependent photodynamic therapy (PDT).Methods: An integrated iridium oxide (IrO2)-manganese dioxide (MnO2) nanotheranostic agent was fabricated through bovine serum albumin (BSA)-based biomineralization of Ir3+ and Mn2+. BSA was first covalently modified with chlorin e6 (Ce6), and used to fabricate multifunctional BSA-Ce6@IrO2/MnO2 nanoparticles (NPs) for computed X-ray tomography (CT) and photoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…In prostate cancer, PLIN3 upregulation has been associated with poor prognosis in patients [ 88 ]. Moreover, elevated PLIN3 expression has recently been related to poor prognosis of lung adenocarcinoma, whereas ablation of PLIN3 inhibited the invasion ability of lung adenocarcinoma cells [ 89 ].…”
Section: Perilipins In Cancer: the Unrevealed Role Of Plin5mentioning
confidence: 99%
“…In prostate cancer, PLIN3 upregulation has been associated with poor prognosis in patients [ 88 ]. Moreover, elevated PLIN3 expression has recently been related to poor prognosis of lung adenocarcinoma, whereas ablation of PLIN3 inhibited the invasion ability of lung adenocarcinoma cells [ 89 ].…”
Section: Perilipins In Cancer: the Unrevealed Role Of Plin5mentioning
confidence: 99%
“…MnO 2 in the composite can produce O 2 by decomposing H 2 O 2 overcoming the hypoxia, thus enhancing the efficacy of PDT, and the released Mn2 + ions can act as contrast agents for magnetic resonance imaging (MRI). In vitro and in vivo evaluation showed that this multifunctional nanotheranostic is an "all in one system" offering highly effective synergistic therapy for photothermal therapy (PTT), PDT, and excellent CT/MRI/PA trimodal imaging (Figure 3) [62].…”
Section: Natural Polymers In Nanotheranostic Agent Design 221 Albuminmentioning
confidence: 99%
“…The biomineralized organic–inorganic composite nanoprobes have attracted more and more attention because of their strong light absorption, easy regulation, good biocompatibility, high photothermal stability, and versatility. [ 183 ]…”
Section: Application Of Nanoparticle Drug Delivery Systems Based On Bmentioning
confidence: 99%